Design and fabrication of gas cell targets for laboratory astrophysics experiments on the Orion high-power laser facility. (25th September 2017) - Spindloe, C.; Wyatt, D.; Astbury, S.; Swadling, G. F.; Clayson, T.; Stehlé, C.; Foster, J. M.; Gumbrell, E.; Charles, R.; Danson, C. N.; Brummitt, P.; Suzuki-Vidal, F.
Abstract : This paper describes the design and fabrication of a range of 'gas cell' microtargets produced by the Target Fabrication Group in the Central Laser Facility (CLF) for academic access experiments on the Orion laser facility at the Atomic Weapons Establishment (AWE). The experiments were carried out by an academic consortium led by Imperial College London. The underlying target methodology was an evolution of a range of targets used for experiments on radiative shocks and involved the fabrication of a precision machined cell containing a number of apertures for interaction foils or diagnostic windows. The interior of the cell was gas-filled before laser irradiation. This paper details the assembly processes, thin film requirements and micro-machining processes needed to produce the targets. Also described is the implementation of a gas-fill system to produce targets that are filled to a pressure of 0.1–1 bar. The paper discusses the challenges that are posed by such a target.